Filhos, família e ambientes honestos: gênero, sexualidade e (des)criminalização do consumo de drogas / Children, family and honest environments: gender, sexuality and (de)criminalization of drug possession - Maques de Mello, Breno; Soeiro Souza, Tuanny (Revista Direito e Práxis, 2020)
DOI: 10.1590/2179-8966/2020/50447 Resumo O presente artigo objetiva analisar diferentes modos como gênero e sexualidade operam nos votos dos ministros do Supremo Tribunal Federal acerca da (des)criminalizaçãodo porte pessoal de drogas, por ocasião do Recurso Extraordinário 635.659/2011. Para tanto, dedica-se especialmente à análise da mobilização das categorias “famílias” e “ambientes honestos”, manejadas nos votos dos ministros, correlacionando-as ainda às tomadas de posição de outros agentes de Estado atuantes na controvérsia pública acerca da “questão das drogas” no país. Palavras-chave: Drogas; Gênero; Sexualidade. Abstract The following paper aims to analyze the different ways in which the terms gender and sexuality are operated in the decisions of the members of the Brazilian Supreme Court when it comes to the case of (de)criminalization of drug possession for personal use specifically in the "Recurso Extraordinário" 635.659/2011 (a special kind of appeal directed only to the Supreme Court). To reach this goal, we give special attention to the categories "family" and "honest environment", which are mentioned in the rulings of the members, and correlate this analysis with the positions of other State agents when it concerns the matter of drugs in Brazil. Keywords: Drugs; Gender; Sexuality.